Climate Change and Its Impacts Risks and Inequalities (Climate Change Management,, 2018)
Responding to a need for a deeper and more nuanced understanding of the consequences of climate change, this book brings experts in climate science, engineering, urban planning, and conservation biology into conversation with scholars in law, geography, anthropology and ethics. It provides insights into how climate change is conceptualized in different fields. The book also aims to contribute to developing successful and multifaceted strategies that promote global, intergenerational and environmental justice. Among the topics addressed are the effects of climate change on the likelihood and magnitude of natural hazards, an assessment of civil infrastructure vulnerabilities, resilience assessment for coastal communities, an ethical framework to evaluate behavior that contributes to climate change, as well as policies and cultural shifts that might help humanity to respond adequately to climate change.